Modernity's Classics - Humphreys, Sarah C.; Wagner, Rudolf G.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book presents critical studies of modern reconfigurations of conceptions of the past, of the 'classical', and of national heritage. Its scope is global (China, India, Egypt, Iran, Judaism, the Greco-Roman world) and inter-disciplinary (textual philology, history of art and architecture, philosophy, gardening). Its emphasis is on the complexity of the modernization process and of reactions to it: ideas and technologies travelled from India to Iran and from Japan to China, while reactions show tensions between museumization and the recreation of 'presence'. It challenges readers to rethink the assumptions of the disciplines in which they were trained
Part I: Anchoring Modernity -- The Making of New Delhi. Classical Aesthetics, (3z(BOriental(3y (BTradition and Architectural Practice: a Transcultural View -- Classics in the Garden: Suppers in an Earthly Paradise -- A Classic Paving the Way to Modernity: The Ritual of Zhou in the Chinese Reform Debate since the Taiping Civil War -- Modernity$1 (Bs Islamicist: Sayyid Qutb$1 (Bs Theocentric Reconstruction of Sovereignty -- Part II: Repositioning Texts -- Classical Scholarship and Arab Modernity -- The Septuagint as a Jewish Classic -- Phenomenon and Reference: Revisiting Parmenides, Empedocles, and the Problem of Rationalization -- Towards an Anthropology of Reading -- Part III: Reconstructing Pastness -- The Ruins of the Others: History and Modernity in Iran -- Making New Classics: the Archaeology of Luo Zhenyu and Victor Segalen -- Homer, Skepticism, and the History of Philology -- Naked Presence and Disciplinary Wording -- Middling Ages and Living Relics as Objects to Think with: Two Figures of the Historical Imagination.s
Keywords: Social sciences; Humanities; Archaeology; Social Sciences; Cultural Studies; Classical Studies; Archaeology